A systematic review and quantitative appraisal of fMRI studies of verbal fluency: Role of the left inferior frontal gyrus - Costafreda, Sergi G.; Fu, Cynthia H.Y.; Lee, Lucy; Everitt, Brian; Brammer, Michael J.; David, Anthony S. (Human brain mapping, 2006)
The left inferior frontal gyrus (LIFG) has consistently been associated with both phonologic and semantic operations in functional neuroimaging studies. Two main theories have proposed a different functional organization in the LIFG for these processes. One theory suggests an anatomic parcellation of phonologic and semantic operations within the LIFG. An alternative theory proposes that both processes are encompassed within a supramodal executive function in a single region in the LIFG. To test these theories, we carried out a systematic review of functional magnetic resonance imaging studies employing phonologic and semantic verbal fluency tasks. Seventeen articles meeting our pre‐established criteria were found, consisting of 22 relevant experiments with 197 healthy subjects and a total of 41 peak activations in the LIFG. We determined 95% confidence intervals of the mean location (x, y, and z coordinates) of peaks of blood oxygenation level‐dependent (BOLD) responses from published phonologic and semantic verbal fluency studies using the nonparametric technique of bootstrap analysis. Significant differences were revealed in dorsal–ventral (z‐coordinate) localizations of the peak BOLD response: phonologic verbal fluency peak BOLD response was significantly more dorsal to the peak associated with semantic verbal fluency (confidence interval of difference: 1.9–17.4 mm). No significant differences were evident in antero–posterior (x‐coordinate) or medial–lateral (y‐coordinate) positions. The results support distinct dorsal–ventral locations for phonologic and semantic processes within the LIFG. Current limitations to meta‐analytic integration of published functional neuroimaging studies are discussed. Hum Brain Mapp, 2006. © 2006 Wiley‐Liss, Inc.